2012
DOI: 10.1177/030006051204000525
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum Interleukin-34 in Patients with Coronary Artery Disease

Abstract: OBJECTIVE: This study investigated levels of interleukin (IL)-34, a proinflammatory cytokine, in patients with coronary artery disease (CAD). METHODS: Following coronary artery angiography, 91 patients with CAD (including stable and unstable angina pectoris) were divided into two groups, the CAD group (coronary artery stenosis ≥ 50%) and the control group (coronary artery stenosis < 50%). Serum levels of factors including IL-34 and high sensitivity C-reactive protein (hs-CRP) were measured. RESULTS: IL-34 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 13 publications
4
20
0
Order By: Relevance
“…On the other hand, our present study demonstrated that higher serum IL-34 levels were associated with more severe coronary artery disease, which is in accordance with the results of a previous study with limited sample size that including only those subjects who had CAD20. Furthermore, another study illustrated that serum IL-34 may be superior to CRP as a potential inflammatory biomarker predicting the risk of vascular diabetic complications21.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, our present study demonstrated that higher serum IL-34 levels were associated with more severe coronary artery disease, which is in accordance with the results of a previous study with limited sample size that including only those subjects who had CAD20. Furthermore, another study illustrated that serum IL-34 may be superior to CRP as a potential inflammatory biomarker predicting the risk of vascular diabetic complications21.…”
Section: Discussionsupporting
confidence: 92%
“…CSF‐1 was detectable in 100% of serum samples, whereas IL‐34, of note, was not measurable in any patient, neither in healthy patients nor in those with periodontal disease. Others have also been unable to detect circulating IL‐34 in healthy patients and in those with osteoarthritis, whereas measurable levels in circulation have been found in patients with RA, 22 coronary artery disease, 46 and obesity 47 . This discrepancy could partially be explained by the different diseases or use of assay kits with differences in the sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying pathological process of CAD is atherosclerosis, which is characterized by chronic inflammation due primarily to the deposit of oxidized lipids on the inner layer of the arterial wall. Studies have indicated that inflammation-related genes may be associated with CAD risk (Xie et al, 2012;Li et al, 2012;Kroeger et al, 2012;Kim et al, 2012;LaFramboise et al, 2012).…”
Section: Introductionmentioning
confidence: 99%